Mechanism of cotton resistance to abiotic stress, and recent research advances in the osmoregulation related genes - Saud, Shah; Wang, Lichen (Frontiers in Plant Science, 2022)
With the shortage of global water resources, soil salinization, frequent extreme weather and other threats, as well as the increasing contradiction between grain and cotton for land, the demand for cotton resistance is getting higher and higher. In this paper, the stress resistance of cotton under abiotic stress, the development, utilization and seed breeding of cotton with stress resistance were reviewed, and proposed the existing problems and the development direction of cotton with stress resistance breeding in the future were proposed.